A chance to improve the therapy of schizophrenia? A review of research on omega-3 essential fatty acids supplementation - Kokoszka, Andrzej (Przewodnik Lekarza/Guide for GPs, 2007)
Review of RCT with placebo indicates that supplementation with omega-3 essential fatty acids is useful in depression, whereas in schizophrenia it is less unequivocal. However, taking into account the benefits of this supplementation for lipid metabolism, which is frequently disturbed in schizophrenia, supplementation with this product seems to be justified in this condition. Moreover, the supplementation of the pharmacological treatment of depression and schizophrenia with omega-3 essential fatty acids is recommended by a subcommittee of the American Psychiatric Association.